Approaches, Strategies, and Models of Moral Education in Indonesia: A Literature Review - Ni Wayan Asri Undayani; Rizka Aluna; Fitriani Fitriani; Lalu Sumardi (Balai Publikasi Indonesia, 2026)
Moral education serves as a critical foundation in shaping a young generation with integrity, resilience, and social responsibility. Amid the challenges of globalization, digital disruption, and a crisis of values among adolescents, the urgency to strengthen moral education has become increasingly evident. This study aims to identify the approaches, strategies, and models of moral education implemented in the Indonesian educational context during the 2020–2025 period. A Systematic Literature Review (SLR) method was employed, based on the PRISMA protocol, by analyzing 30 scholarly articles sourced from Google Scholar, Garuda, and reputable national journals. The findings indicate that moral education approaches are diverse, ranging from religious, constructivist, and value-affective, to visionary-systemic approaches. The strategies identified include role modeling, habituation, reflective projects, and school-family collaboration. Prominent models include religious habituation, transformational character education, cognitive moral dilemmas, and the family-based character model. These approaches have demonstrated high effectiveness when implemented contextually and consistently. Nevertheless, challenges such as low teacher competence, lack of cross-environment synergy, and the influence of digital media remain significant obstacles. This study contributes to mapping moral education practices at the national level and serves as a reference for curriculum development, teacher training, and the formulation of more adaptive and collaborative character education policies.